Annual review of Golf coaching 2011 (International Journal of Sports Science and Coaching, 2012)
The target article in this issue of the Annual Review of Golf Coaching is entitled "Accreditation of PGA Master Coaches". One of the commentators on this article is a PGA of Great Britain and Ireland member, Neil Plimmer, who describes himself as "more of a performance coach than a technical `how to` coach" (p. 126) and this is apparent from his list of his continual professional development (CPD) over the last eight years (p. 128). At the PGA of Great Britain and Ireland Golf Show in Harrogate this October, the author led a seminar for PGA members on "What the PGA Professional can Learn from the Business Coach" with the aim of taking some key coaching theory such as the GROW model and the Inner Game and show how applicable it is to PGA professionals who can use the principles to carry out their role as coach, club pro, manager, etc. Areas of discussion included self-awareness, authenticity, responsibility, trust, respect, caring, communication and questioning.